This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution...
Toggle latex and copy this solution into your's:
E = d t d ϕ = d t d ( A B ) = A d t d B
E = π r 2 d t d B
Now resistance of the wire, R = A ρ l
R = π a 2 p ( 2 π r )
i = R E = ( π r a 2 ) ( 2 p 1 ) ( d t d B ) → 1
Mass of the wire, m = ( π a 2 ) ( 2 π r ) ( d )
π r a 2 = 2 π d m → 2
Replacing 2 in 1 ,
i = ( 4 π d p m ) ( d r d B )
Problem Loading...
Note Loading...
Set Loading...
E = d ¢ / d t , i = E / R = ( 1 / R ) ∗ d / d t ( B A ) = ( A / R ) ∗ d B / d t where ¥ r 2 area of the loop of radius r and resistance R length= 2 ¥ r and area of cross section= ¥ a 2 . .. R = ( p l / ( ¥ a 2 ) further mass of the wire = ( ¥ a 2 ) ( 2 ¥ r ) ( d ) substituting the value of R in the first eqn we get i = ( ( ¥ a 2 ) ( ¥ r 2 ) / ( 4 ¥ p ) ) ∗ d B / d t ...therefore replacing the required value to get in terms of m ..we get finally i = ( m / 4 ¥ p d ) ∗ d b / d t ..